2017
DOI: 10.1186/s13040-017-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Proteome Database

Abstract: BackgroundRecently we surveyed the dark-proteome, i.e., regions of proteins never observed by experimental structure determination and inaccessible to homology modelling. Surprisingly, we found that most of the dark proteome could not be accounted for by conventional explanations (e.g., intrinsic disorder, transmembrane domains, and compositional bias), and that nearly half of the dark proteome comprised dark proteins, in which the entire sequence lacked similarity to any known structure. In this paper we will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 13 publications
4
38
0
Order By: Relevance
“…The focus of this study however, was the Homo Sapiens and other model organisms where it can be concluded that the amount of dark proteome present in them is still high, whereas in higher eukaryotes like mouse and human, it is around 50%. The results presented above are consistent with previous works (6,23), since Arabidopsis dark proteins are mainly located in extracellular space, cellular membrane and endoplasmic reticulum membranes. C. Elegans dark proteins are present again in cell membrane where they are secreted.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The focus of this study however, was the Homo Sapiens and other model organisms where it can be concluded that the amount of dark proteome present in them is still high, whereas in higher eukaryotes like mouse and human, it is around 50%. The results presented above are consistent with previous works (6,23), since Arabidopsis dark proteins are mainly located in extracellular space, cellular membrane and endoplasmic reticulum membranes. C. Elegans dark proteins are present again in cell membrane where they are secreted.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning functions, the results confirmed that dark proteins perform a wide spectrum of functions depending on the organism in question, being more focused in simpler organisms and wider in higher organisms (6). Again, it was sound that a vast amount of then is programmed to live outside the cell, where many are associated with secretion (through secretory glands and guts) or with extracellular areas in tissues, being an indicator that they possibly are designed for being defensive agents against external threats such as bacteria and/or virus.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…According to the Protein Structure group, the dark proteome consists of proteins for which the experimental structure has never been determined and which are inaccessible to homology modeling. More than half of dark proteins are not intrinsic disorder proteins, have no transmembrane domain, and have a low compositional bias, as shown by Perdigão et al 35,36 .…”
Section: Resultsmentioning
confidence: 91%